Mapping Research on Bambara Groundnut (Vigna subterranea (L.) Verdc.) in Africa: Bibliometric, Geographical, and Topical Perspectives - El Bilali, Hamid; Kiebre, Zakaria; Nanema, Romaric Kiswendsida; Dan Guimbo, Iro; Rokka, Veli-Matti; Gonnella, Maria; Tietiambou, Sheirita Reine Fanta; Dambo, Lawali; Nanema, Jacques; Grazioli, Francesca; Acasto, Filippo (MDPI, 2024)
While Bambara groundnut (Vigna subterranea (L.) Verdc.) originates from Africa and the list of producers is topped by African countries, it is not clear whether research is developed enough to support crop promotion in the continent. Thus, this systematic review of 180 articles presents a comprehensive summary of research on Bambara groundnut (BGN) in Africa. The paper addresses bibliographical metrics, the geographic distribution of the research and themes covered (viz., food and nutrition security, climate resilience, and livelihoods). The analysis shows that BGN can help address different challenges in Africa, such as food and nutrition insecurity and poverty. However, it also highlights gaps in the research from geographical and thematic standpoints. Geographically speaking, the most important producers of BGN in Africa are not sufficiently covered in the research; instead, it is mainly carried out in Nigeria and South Africa. Thematically speaking, the gaps are related to economics and social sciences, the use of BGN in animal production, processing and marketing, irrigation, contribution to climate resilience and livelihoods, and health benefits. Collaborative research and knowledge sharing, including among producing countries and those leading the research field, are highly needed to unlock the potential of BGN and boost its contribution to sustainable development in Africa.
Keywords: neglected and underutilised species; NUS; orphan crops; Bambara nut; Bambara bean; legume; food security; climate change; livelihoods; SUSTLIVES